Interest of the Company- the Discussion on Axiological Choices - Stefanicki, Robert (Review of European and Comparative Law, 2022)
The obligation to act professionally and loyal to the managed corporation is a statutory component of the organizational relationship and expresses the essence of these bonds and the sense of entrusting the values of the company to these hubs for the purpose of its proper management. The sources of the administrator’s duties cannot be limited to respecting statutory injunctions and prohibitions, since they designate only border points. They do not constitute a casuist regulation of all situations. Assuming the legislator’s praxeological and axiological rationality in the process of legislating, it would be necessary to involve a lack of due professional diligence on the basis of civil law liability. However, most courts, as well as the majority of the representatives of doctrine, do not recognize the basis of this responsibility in the mere failure to observe the standards in question, regardless of the seriousness of negligence or inefficiency in the exercise of functions.